P041: Does the involvement of learners in emergency department patient assessments result in an increased rate of short-term return visits?. (May 2019) - Elliott, C.; Chen, K.; Fitzpatrick, T.
Abstract : Introduction : Learners, ether medical students or residents, often provide the initial assessment of patients visiting the Emergency Department (ED). Their involvement in ED patient care has been shown to increase length of stay, time to disposition decision, utilization of imaging and admission rates. It is unclear, however, if learners have an impact on the rate of short-term unscheduled return visits. The objective of this study was to determine if the involvement of learners in ED visits increases the rate of short-term unscheduled return visits.Methods : This study was a retrospective analysis of ED visit data at a single tertiary care center over a one-year period. Short-term unscheduled return visits (return visits) were defined as ED visits presenting within 72 hours of discharge from an initial non-admit ED visit and resulting in an admission to an inpatient unit on the second visit. The primary outcome was the rate of return visits for each staff physician, with and without learners involved during the initial visit. The secondary outcome assessed the interaction of level of training (medical student year 3, 4, resident year 1, 2, etc.) on return visit rates. For the primary outcome, statistical analysis was with a Wilcoxon Matched Pairs test; staff alone vs with learners. A Kruskal-Wallis test was used to compare learner level of training.Results : Return visits accounted for 1858 (1.09%) of all visits (N = 172494) to this tertiary care ED over the one-year study period. Return visits were statistically more likely when learners were involved in the initial ED visit (1.16%, CI 0.12), compared to initial visits seen by staff physicians alone (0.88%, CI 0.09) (p < 0.0001). Return rates were statistically higher for PGY2 (1.67% CI 0.35) and PGY3 (1.66% CI 0.28) residents compared to staff physicians alone (p < 0.0001). There was no difference in return visit rates between staff physicians and third year medical students (1.07% CI 0.27), fourth year medical students (1.21% CI 0.37), PGY1 (1.42% CI 0.22), PGY4 (1.23% CI 0.54) or PGY5 (1.33% CI 0.49) residents.Conclusion : This study demonstrated that the involvement of learners in ED patient assessments increased the rate of short-term unscheduled return visits. Moreover, return visit rates were highest for PGY2 and PGY3 residents. Further work is needed to understand the factors that contribute to this phenomenon.